Molecular epidemiology and clinical characteristics of the type VI secretion system in Klebsiella pneumoniae causing abscesses - Liu, Peilin; Yang, Awen; Tang, Bin; Wang, Zhiqian; Jian, Zijuan; Liu, Yanjun; Wang, Jiahui; Zhong, Baiyun; Yan, Qun; Liu, Wenen (Frontiers in Microbiology, 2023)
Purpose: The type VI system (T6SS) has the potential to be a new virulence factor for hypervirulent Klebsiella pneumoniae (hvKp) strains. This study aimed to characterize the molecular and clinical features of T6SS-positive and T6SS-negative K. pneumoniae isolates that cause abscesses. Patients and methods: A total of 169 non-duplicate K. pneumoniae strains were isolated from patients with abscesses in a tertiary hospital in China from January 2018 to June 2022, and clinical data were collected. For all isolates, capsular serotypes, T6SS genes, virulence, and drug resistance genes, antimicrobial susceptibility testing, and biofilm formation assays were assessed. Multilocus sequence typing was used to analyze the genotypes of hvKp. T6SS-positive hvKp, T6SS-negative hvKp, T6SS-positive cKP, and T6SS-negative cKP (n=4 strains for each group) were chosen for the in vivo Galleria mellonella infection model and in vitro competition experiments to further explore the microbiological characteristics of T6SS-positive K. pneumoniae isolates. Results: The positive detection rate for T6SS was 36.1%. The rates of hvKp, seven virulence genes, K1 capsular serotype, and ST23 in T6SS-positive strains were all higher than those in T6SS-negative strains (P<0.05). Multivariate logistic regression analysis indicated that the carriage of aerobactin (OR 0.01) and wcaG (OR 33.53) were independent risk factors for T6SS-positive strains (P<0.05). The T6SS-positive strains had a stronger biofilm-forming ability than T6SS-negative strains (P<0.05). The T6SS-positive and T6SS-negative strains showed no significant differences in competitive ability (P=0.06). In the in vivo G. mellonella infection model, the T6SS(+)/hvKP group had the worst prognosis. Except for cefazolin and tegacyclin, T6SS-positive isolates displayed a lower rate of antimicrobial resistance to other drugs (P<0.05). The T6SS-positive isolates were more likely to be acquired from community infections (P<0.05). Conclusion: K. pneumoniae isolates causing abscesses have a high prevalence of T6SS genes. T6SS-positive K. pneumoniae isolates are associated with virulence, and the T6SS genes may be involved in the hvKp virulence mechanism.